The Boundless - Oppel, Kenneth, 1967- (New York : Simon & Schuster Books for Young Readers, 2014)
Aboard "The Boundless," the greatest train ever built, on its maiden voyage across Canada, teenaged Will enlists the aid of a traveling circus to save the train from villains.
Keywords: Railroad trains -- Fiction; Circus -- Fiction; Adventure and adventurers -- Fiction; Canada -- History -- 1867-1914 -- Fiction